PERLAWANAN MASYARAKAT KOREA SELATAN MENUJU GERBANG DEMOKRASI TAHUN 1980 - Retno Ayu Oktaviani; Agus Mulyana (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2018)
The research was an in-depth study concerning the events of Gwangju society’s resistance against the authoritarian Government that occurred in 1980. Problem formulation is “how has Gwangju Democratization Movement in 1980 occurred?”. Researchers conducted historical methods, including collecting writing sources through literature study, critic source, interpretation or source analysis and historiography. The results found that democracy in South Korea was hampered Confucianism ideology which then led South Korea became authoritarian Government. The movement of students and Gwangju’s society were a peaceful act, but military responded back with a violation and the Government manipulate media to cover up an event so it cannot be used as an opportunity for North Korea. Gwangju democratization movement became ‘the gate’ in other regions of South Korea to realize democracy